Optimización de la metodología de corte de tubería flexible en las actividades de intervención de pozos que desarrolla la empresa halliburton en Colombia, mediante una simulación numérica (2019)
This project seeks the optimization of the flexible pipe cutting methodology in well intervention activities developed by the HALLIBURTON company in Colombia, using a numerical simulation, analyzing the variables: total cut length, pull test and period between cuts, from 10 scenarios, in order to perform a complete analysis of these variables to proceed to design a new methodology, which optimizes what is being implemented at this time. And their respective financial analysis is performed to find out if this designed methodology is economically attractive to the support company.